Find two numbers that sum to -6 and which multiply to 5.
The answer to that is -1 and -5
So: x2 - 6x + 5 = 0 implies (x - 1)*(x - 5) = 0
which is true if and only if x - 1 = 0 or x - 5 = 0
which is true if and only if x = 1 or x = 5
It is: 3x2+6x-11 = 0
y=6x² is already solved. the parabola will touch the x-axis at x=0.
3x(2x + 1)
6x-2=x+135x=15x=3
The answer is x = 2.
x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4
It is: 3x2+6x-11 = 0
16x+9 without the rest of the equation, what this equals, I can't solve
y=6x² is already solved. the parabola will touch the x-axis at x=0.
If 6x + 10 = 11x , then x=2.
3x(2x + 1)
6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6
6x-2=x+135x=15x=3
The answer is x = 2.
-6x + 12y = -102 -6x = -12y - 102 x = 2y + 17
-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2
There is no non-trivial equivalent.